The Association of Sarcopenia and Visceral Obesity with Lean Nonalcoholic Fatty Liver Disease in Chinese Patients with Type 2 Diabetes Mellitus - Xingxing Zhang; Zhiying He; Qiya Si; Xiang Hu; Lijuan Yang; Xiao Gu; Linjia Du; Lei Wang; Linyu Pan; Yingqian Li; Jing Li; Bo Yang; et al. (Journal of Diabetes Research)
Background. Few studies have specifically observed the relationship of sarcopenia, visceral obesity, or their joint effects with lean NAFLD in patients with diabetes. We aimed to investigate the associations of lean NAFLD with sarcopenia, visceral obesity, and sarcopenic visceral obesity (SV) in Chinese patients with type 2 diabetes mellitus (T2DM). Methods. Altogether, 1,112 T2DM patients with BMI <25 kg/m2 were enrolled, and 33.18% of them were diagnosed with lean NAFLD by abdominal ultrasonography. Body composition markers were measured by bioelectrical impedance (BIA). Skeletal muscle mass index (SMI) was calculated as appendicular skeletal muscle mass (ASM) divided by weight, and sarcopenia was defined as SMI<1 standard deviation SD below the sex-specific average for a young reference population. Visceral obesity was defined as visceral fat area VFA≥100 cm2. Participants were categorized into one of the four body composition groups: nonsarcopenia/nonvisceral obesity (NN), nonsarcopenia/visceral obesity (NV), sarcopenia/nonvisceral obesity (SN), and SV. Results. Compared to those in the NN group, patients in the NV and SN groups had a higher risk of lean NAFLD after full adjustments (NV: OR=1.74; 95% CI: 1.09, 2.78; SN: OR =2.07; 95% CI: 1.23, 3.46). Of note, patients in the SV group had the highest odds of lean NAFLD (OR=3.29; 95% CI: 2.10, 5.17). There were no significant interaction effects between sarcopenia and metabolic risk factors on prevalent lean NAFLD. Conclusions. The current study demonstrated that SV was more closely associated with higher prevalent lean NAFLD than sarcopenia or visceral obesity alone in Chinese patients with T2DM. Besides, the harmful effect of sarcopenia on lean NAFLD was not influenced by visceral obesity or other metabolic risk factors. We hypothesize that increasing skeletal muscle mass more than just reducing visceral fat might be more optimal for the prevention and management of lean NAFLD, which needs further investigation in future studies.